From Democritus to Bertrand Russell and Back - Motte, André (Peitho. Examina Antiqua, 2019)
Although Bertrand Russell is probably most famous for his “logical atomism,” it is his ethical thought that this article will attempt to contrast with the ethics of the founder of the ancient atomism: Democritus of Abdera. Russell has himself suggested certain affinity here. More concerned with practice than theory, both philosophers advocate a certain teleological and eudemonistic morality; furthermore, they both adopt the same approaches to various related topics. Yet, what had only been outlined by Democritus was extensively developed by Russell. Hence, it is worth examining whether there is any deeper common ground between the two: can Russell’s clarity throw some light on Democritus’ fragments?